2014
DOI: 10.1142/s0217984914500638
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior and constitutive modeling of magnesium alloys AZ91D and AZ31B under high strain rate compressive loading

Abstract: The dynamic stress–strain characteristics of magnesium alloys have not been sufficiently studied experimentally. Thus, the present work investigated compressive dynamic stress–strain characteristics of two representative magnesium alloys: AZ91D and AZ31B at high strain rates and elevated temperatures. In order to use the stress–strain characteristics in numerical simulations to predict the impact response of components, the stress–strain characteristics must be modeled. The most common approach is to use accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…They observed that increasing the rotational speed above 1400 rpm caused void defect to form in the stir zone. Increase in grain size and in dislocation density in the stir zone was observed with increase in the rotational speed [7].…”
Section: Introductionmentioning
confidence: 84%
“…They observed that increasing the rotational speed above 1400 rpm caused void defect to form in the stir zone. Increase in grain size and in dislocation density in the stir zone was observed with increase in the rotational speed [7].…”
Section: Introductionmentioning
confidence: 84%
“…This is because it can accurately predict model parameters with minimal effort and is therefore incorporated into most of the available FE tools. The JC model is adequate to define the material behaviour during the FSW/FSP as a process with intense plastic deformation at a high strain rate because JC constants for every single material are established from the results of high strain rate tests [33]. The material behaviour for thermal simulation of FSW for AZ91 Mg alloy is modelled using the JC material model by Fashami et al [34] and Hoda et al [27] due to the robustness analysis of its parametric campaign.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The tensile properties of sheet metals at high or intermediate strain rate are important since the dynamic behavior of a material is different from its static behavior because of the strain rate effect . During the sheet metal forming processes the thickness distribution and the flow stress of sheet metals change with the plastic strain and the residual stress .…”
Section: Introductionmentioning
confidence: 99%
“…The tensile properties of sheet metals at high or intermediate strain rate are important since the dynamic behavior of a material is different from its static behavior because of the strain rate effect. [1][2][3][4] During the sheet metal forming processes the thickness distribution and the flow stress of sheet metals change with the plastic strain and the residual stress. [5] Most experiments to obtain the tensile properties at intermediate strain rate have been thus far carried out by using specimens without considering the pre-strain from the forming process.…”
Section: Introductionmentioning
confidence: 99%